Opini Publik Kota Serang Mengenai Reputasi Unilever di Tengah Dinamika Isu Boikot - Zahrah Mahfudzah Firdaus; Noerma Kurnia Fajarwati; Meiby Zulfikar; April Laksana; Arfian Suryasuciramdhan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The boycott of companies suspected of having ties to Israel has drawn public attention, including Unilever. This research was motivated by the need to understand how Unilever, impacted by the boycott, is attempting to restore its reputation in the eyes of the public. Specifically, this research aims to analyze how the people of Serang City respond to these efforts amidst the turmoil of this sensitive issue. The study used a quantitative approach based on the S-O-R (Stimulus-Organism-Response) theory. Data were collected through questionnaires distributed to 400 respondents in Serang City. The main focus of the analysis was on three Unilever strategies: a statement of non-involvement in the genocide, providing aid to refugees in Egypt, and offering product discounts at local retailers. The S-O-R theory was used to observe how the company's communication stimuli generate psychological responses and public attitudes toward brand reputation. The study results showed that 68.12% of respondents responded positively to Unilever's efforts, although this figure only slightly exceeded the minimum threshold set in the hypothesis. The majority of the public is more familiar with discount efforts than humanitarian aid or official clarification. Therefore, information transparency and strengthened crisis management need to be optimized to clarify Unilever's position and sustainably strengthen the company's reputation amidst sensitive social and political issues.